Constructing grounded theory - Charmaz, Kathy, 1939- (2014)
"Kathy Charmaz presents the definitive guide to doing grounded theory from a constructivist perspective. This second edition of her groundbreaking text retains the accessibility and warmth of the first edition whilst introducing cutting edge examples and practical tips."--Page 4 of cover.
An invitation to grounded theory -- Gathering rich data -- Crafting and conducting intensive interviews -- Interviewing in grounded theory studies -- The logic of grounded theory coding practices and initial coding -- Focused coding and beyond -- Memo-writing -- Theoretical sampling, saturation, and sorting -- Reconstructing theorizing in grounded theory studies -- Symbolic interactionism and grounded theory -- Writing the draft -- Reflecting on the research process.
Includes bibliographical references (pages 346-378) and index.
Keywords: Grounded theory; Grounded Theory; Grounded theory; Grounded theory; Qualitative Inhaltsanalyse; Kwalitatieve methoden; Sociale wetenschappen; Theorievorming; Gidsen (vorm)